Prospects of breeding biofortified pearl millet with high grain iron and zinc density - Velu, G.; Rai, K. N.; Muralidharan, V.; Kulkarni, V. N.; Longvah, T.; Reveendran, T. S. (Wiley, 2007)
Development of crop cultivars with elevated levels of micronutrients is being increasingly recognized as one of the approaches to provide sustainable solutions to various health problems associated with micronutrient malnutrition, especially in developing countries. To assess the prospects of this approach in pearl millet (Pennisetum glaucum), a diverse range of genetic materials, consisting of 40 hybrid parents, 30 each of population progenies and improved populations, and 20 germplasm accessions, was analysed for grain iron (Fe) and zinc (Zn) content, deficiencies of which adversely affect human health. Based on the mean performance in two seasons at ICRISAT, Patancheru, India, large variability among the entries was found, both for Fe (30.1–75.7 mg/kg on dry weight basis) and Zn (24.5–64.8 mg/kg). The highest levels of grain Fe and Zn were observed in well‐adapted commercial varieties and their progenies, and in the parental lines of hybrids, which were either entirely based on iniari germplasm, or had large components of it in their parentage. There were indications of large within‐population genetic variability for both Fe and Zn. The correlation between Fe and Zn content was positive and highly significant (r = 0.84; P < 0.01). These results indicate that there are good prospects of simultaneous selection for both micronutrients, and that selection within populations, especially those with the predominantly iniari germplasm, is likely to provide good opportunities for developing pearl millet varieties and hybrid parents with significantly improved grain Fe and Zn content in pearl millet.